2018
DOI: 10.3389/fneur.2018.00308
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Outcome in Patients With Acute Ischemic Stroke Based on Initial Severity and Improvement in the First 24 h

Abstract: IntroductionStroke severity measured by the baseline National Institutes of Health Stroke Scale (NIHSS) is a strong predictor of stroke outcome. Early change of baseline severity may be a better predictor of outcome. Here, we hypothesized that the change in NIHSS in the first 24 h after stroke improved stroke outcome prediction.Materials and methodsPatients from the Leuven Stroke Genetics Study were included when the baseline NIHSS (B-NIHSS) was determined on admission in the hospital and NIHSS after 24 h coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
79
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(95 citation statements)
references
References 23 publications
(27 reference statements)
11
79
1
4
Order By: Relevance
“…On the other hand, according to the National Institutes of Health Stroke Scale (NIHSS), 24 hours post onset of symptoms is the time point at which the clinical condition must be assessed when evaluating the effects of a given treatment at the acute phase of stroke. Lending further support, neurological examination at 24 hours has also been reported to predict functional outcomes at 1 month and 90 days post stroke.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, according to the National Institutes of Health Stroke Scale (NIHSS), 24 hours post onset of symptoms is the time point at which the clinical condition must be assessed when evaluating the effects of a given treatment at the acute phase of stroke. Lending further support, neurological examination at 24 hours has also been reported to predict functional outcomes at 1 month and 90 days post stroke.…”
Section: Discussionmentioning
confidence: 94%
“…NIHSS scores have shown to be predictive for any vessel occlusions in the anterior circulation, and cut-off values of NIHSS scores >7 from three to six hours of stroke onset provided a predictive value of 84.4% for worsening neurologic functions [22]. In another study [21], major neurological improvements were observed with a NIHSS score of below eight within 24 hours of stroke onset, while a score of ≤ 6 forecasts a favorable neurological recovery [23].…”
Section: Introductionmentioning
confidence: 98%
“…Patients with a National Institute of Health Stroke Scale (NIHSS) score of equal to or less than 7 at the time of admission demonstrate a higher likelihood of making positive neurological progress after an AIS, while NIHSS scores greater than 7 on admission demonstrated a higher probability of worsening neurological function in hemispheric strokes [19,20]. Therefore, the baseline NIHSS, stratified by NIHSS scores of ≤7 and >7 can be used to assess improvement or non-improvement following thrombolytic therapy for AIS [21,22]. NIHSS scores have shown to be predictive for any vessel occlusions in the anterior circulation, and cut-off values of NIHSS scores >7 from three to six hours of stroke onset provided a predictive value of 84.4% for worsening neurologic functions [22].…”
Section: Introductionmentioning
confidence: 99%
“…In another study [21], NIHSS scores turned out to be predictive for any vessel occlusions in the anterior circulation, and cutoff values of NIHSS scores ≥ 7 of 3 to 6 hours of stroke onset provided a predictive value of 84.4% [21]. In another study [20], major neurological improvements were observed below NIHSS of 8 within 24 hours of stroke onset, while a score of < or = 6 forecasts a good recovery [22]. While low and high NIHSS cut-off points are effective predictors for good and poor outcomes, the NIHSS is heavily weighted towards hemispheric stroke [23].…”
Section: Introductionmentioning
confidence: 92%
“…Patients with a National Institute of Health Stroke Scale (NIHSS) score of equal to or less than 7 at the time of admission demonstrate a higher likelihood of making progress after an AIS, while scores greater than 7 on admission demonstrated a higher probability of worsening neurological function in hemispheric stroke [17,18]. Therefore, the baseline NIHSS, stratified by NIHSS scores of ≥ 7 for worsening neurologic functions and ≤ 7 for neurologic improvement can be used to assess improvement or non-improvement following thrombolytic therapy [19,20]. In another study [21], NIHSS scores turned out to be predictive for any vessel occlusions in the anterior circulation, and cutoff values of NIHSS scores ≥ 7 of 3 to 6 hours of stroke onset provided a predictive value of 84.4% [21].…”
Section: Introductionmentioning
confidence: 99%